2019
DOI: 10.1152/ajpheart.00595.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Tobacco smoking induces cardiovascular mitochondrial oxidative stress, promotes endothelial dysfunction, and enhances hypertension

Abstract: Tobacco smoking is a major risk factor for cardiovascular disease and hypertension. It is associated with the oxidative stress and induces metabolic reprogramming, altering mitochondrial function. We hypothesized that cigarette smoke induces cardiovascular mitochondrial oxidative stress, which contributes to endothelial dysfunction and hypertension. To test this hypothesis, we studied whether the scavenging of mitochondrial H2O2 in transgenic mice expressing mitochondria-targeted catalase (mCAT) attenuates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 74 publications
7
118
2
2
Order By: Relevance
“…During this process, O 2 -• and H 2 O 2 are produced, and these species are converted through an iron-catalysed reaction into HO • radical, leading to biological damage. 12,44 The significant elevation of Hb concentration and its related markers that occurred in the smokers group in this study was consistent with other reports. 32,38 This elevation is best explained as a compensatory mechanism that increases Hb concentration because of a lack of oxygencarrying capacity in carboxy-Hb, which results from continuous exposure of the smoker to carbon monoxide that is generated in the cigarette burning process.…”
Section: Discussionsupporting
confidence: 92%
“…During this process, O 2 -• and H 2 O 2 are produced, and these species are converted through an iron-catalysed reaction into HO • radical, leading to biological damage. 12,44 The significant elevation of Hb concentration and its related markers that occurred in the smokers group in this study was consistent with other reports. 32,38 This elevation is best explained as a compensatory mechanism that increases Hb concentration because of a lack of oxygencarrying capacity in carboxy-Hb, which results from continuous exposure of the smoker to carbon monoxide that is generated in the cigarette burning process.…”
Section: Discussionsupporting
confidence: 92%
“…Previous experimental studies have demonstrated that cigarette smoking causes endothelial dysfunction and cardiac hypertrophy through cellular oxidative stress and decreased NO bioavailability 25 . Cigarette smoking is also known to induce mitochondrial oxidative stress, which contributes to the development of hypertension 17 . On the other hand, one previous study reported that CS can induce cardiac hypertrophy without any increase in blood pressure 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic effect between elevated blood pressure and CS exposure has also been reported in epidemiological studies 16 . In addition, CS exposure has been shown to induce cardiovascular oxidative stress 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Complications of hypertension such as atherosclerosis, myocardial I/R injury and hypertrophy, and heart failure are closely associated with cardiomyocyte and endothelial mitochondrial dysfunction [131]. Insufficient energy supply, kinetic imbalance, oxidative damage, abnormal signal transduction, and mitochondrial dysfunction caused by genetic mutations are risk factors for hypertension [132][133][134]. Myocardial hypertrophy associated with hypertension reportedly altered cardiomyocyte phenotype, function, and energy metabolism.…”
Section: Hypertensionmentioning
confidence: 99%